Regional input-output tables and models : interregional trade estimation and input-output modelling based on total use rectangular tables - Sargento, Ana Lúcia Marto (2009)
Tese de doutoramento em Economia (Planeamento e Economia Regional) apresentada à Fac. Economia da Univ. Coimbra